FETO-MATERNAL OUTCOMES OF INDUCTION OF LABOUR IN WOMEN WITH POST-TERM PREGNANCIES - HAMZA , S; FAIZ , S; REHMAN , N; SAEED , N; KHAN, L (Biological and Clinical Sciences Research Journal, 2024)
Post-term pregnancies are associated with increased risks for both maternal and neonatal complications. Labor induction is a common intervention to reduce these risks; however, its outcomes remain variable. Understanding the fetomaternal outcomes of labor induction in post-term pregnancies is crucial for optimizing clinical management and decision-making. Objective: To evaluate the fetomaternal outcomes of labor induction in women with post-term pregnancies presenting at a tertiary care facility. Methods: This descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology from March 2024 to September 2024. A total of 115 women aged 18 to 40 years with postdated pregnancies, regular menstrual cycles, and singleton vertex presentations were enrolled. High-risk pregnancies and those with prior cesarean sections or congenital fetal anomalies were excluded. Labor was induced using sublingual misoprostol (25 μg every four hours for up to four doses). Outcomes, including postpartum hemorrhage (PPH), cesarean delivery, prolonged hospital stay, birth asphyxia, neonatal intensive care unit (NICU) admissions, and meconium aspiration, were assessed. Results: Cesarean sections occurred in 20.9% of cases, and 17.4% experienced PPH. Prolonged hospital stays were recorded in 15.7% of participants. Birth asphyxia was observed in 11.3% of neonates, while 16.5% required NICU admission. Meconium aspiration was noted in 12.2% of cases. No notable associations were found between maternal age or parity and the assessed outcomes (p > 0.05). Conclusion: Labor induction in post-term pregnancies is associated with a higher prevalence of cesarean delivery, PPH, and neonatal complications, including NICU admissions and meconium aspiration. These findings highlight the importance of timely interventions and vigilant monitoring to optimize outcomes in post-term pregnancies.